Intestinal Angiolipofibroma: Clinicopathologic Characteristics of 11 Cases. (September 2020) - Agostini-Vulaj, Diana; Bsirini, Caroline; Drage, Michael G.; Huber, Aaron R.
Mesenchymal lesions of the gastrointestinal tract are generally uncommon compared with epithelial derived entities. Angiolipofibroma describes a rare gastrointestinal tract mesenchymal lesion composed of varied amounts of adipose tissue, fibrous tissue, along with admixed blood vessels. Descriptions of this entity are limited to few case reports describing a total of 5 lesions. Angiolipofibroma represents a benign entity that may uncommonly present as a mass lesion concerning for malignancy. The etiology is unclear; however, these may represent a reactive or hamartomatous process. In this article, we sought to further describe this entity and present an additional 11 cases.